2013
DOI: 10.1515/cclm-2013-0205
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of haemophilia: our experience of 44 cases

Abstract: PD in well-equipped laboratories, and multidisciplinary counselling are an aid to planning reproductive and early therapeutic strategies in families with severe haemophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, in six cases STR preliminary analysis revealed that CV DNA was contaminated by maternal DNA; they included one case of haemophilia (in which the foetus was female), two cases of thalassaemia (in which the paternal mutation was absent) and three cases for which PD was not concluded. In all other cases, including eight twin dichorionic pregnancies, PD was concluded [see also [12][13][14][15]. Finally, in 15 cases, STR analysis revealed non-paternity.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, in six cases STR preliminary analysis revealed that CV DNA was contaminated by maternal DNA; they included one case of haemophilia (in which the foetus was female), two cases of thalassaemia (in which the paternal mutation was absent) and three cases for which PD was not concluded. In all other cases, including eight twin dichorionic pregnancies, PD was concluded [see also [12][13][14][15]. Finally, in 15 cases, STR analysis revealed non-paternity.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, the laboratory must be equipped with adequate quality control programmes [30]. For most diseases we used two different analytical procedures (that have invariably given concordant results), including, where available, linkage analysis [12][13][14][15]31]. Finally, the laboratory must be equipped to perform a preliminary analysis of maternal cell contamination and paternity testing (since in most PDs only parental mutations are analysed).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now clearly established that different clinical phenotypes can emerge from an interaction between genetics and environment, as increasingly recognized for the common hemophilias [104] and also for hemostasis as we age [105]. As such, further advances in genomic technology [84,85] will make it possible to extend the database of mutations of all known hemorrhagic defects, more precisely understand the structure-function relationship of coagulation factors, bridge the gap between genotype and clinical or laboratory phenotype [106], plan specific therapies which are not only more likely to respond according to a specific genotype, but also obtain an early diagnosis during pregnancy or stillbirth, so that the mutation (or the haplotype) can be precisely identified at the time of prenatal diagnosis [107]. Genetic testing by means of high-throughput techniques such as next-generation sequencing will also enable the investigation of multiple coagulation factor genes simultaneously, so that the diffusion of these methods is expected to grow exponentially, even in clinical laboratories, in the next few years.…”
Section: Expert Commentarymentioning
confidence: 99%